Whole Genome Sequencing Reveals Substantial Genetic Structure and Evidence of Local Adaptation in Alaskan Red King Crab - Carl A. St. John; Laura E. Timm; Kristen M. Gruenthal; Wesley A. Larson (Evolutionary Applications)
ABSTRACT High‐latitude ocean basins are the most productive on earth, supporting high diversity and biomass of economically and socially important species. A long tradition of responsible fisheries management has sustained these species for generations, but modern threats from climate change, habitat loss, and new fishing technologies threaten their ecosystems and the human communities that depend on them. Among these species, Alaska's most charismatic megafaunal invertebrate, the red king crab, faces all three of these threats and has declined substantially in many parts of its distribution. Managers have identified stock structure and local adaptation as crucial information to help understand biomass declines and how to potentially reverse them, with regulation and possible stock enhancement. We generated low‐coverage whole genome sequencing (lcWGS) data on red king crabs from five regions: The Aleutian Islands, eastern Bering Sea, northern Bering Sea, Gulf of Alaska, and Southeast Alaska. We used data from millions of genetic markers generated from lcWGS to build on previous studies of population structure in Alaska that used < 100 markers and to investigate local adaptation. We found each of the regions formed their own distinct genetic clusters, some containing subpopulation structure. Most notably, we found that the Gulf of Alaska and eastern Bering Sea were significantly differentiated, something that had not been previously documented. Inbreeding in each region was low and not a concern for fisheries management. We found genetic patterns consistent with local adaptation on several chromosomes and one particularly strong signal on chromosome 100. At this locus, the Gulf of Alaska harbors distinct genetic variation that could facilitate local adaptation to their environment. Our findings support the current practice of managing red king crab at a regional scale, and they strongly favor sourcing broodstock from the target population if stock enhancement is considered to avoid genetic mismatch.